The Implementation of Grew-Deal Nursing Interventions to Achieve Ideal Body Weight in High School Students - Pranata, Andi; Nursasi, Astuti Yuni; Rahmadiyah, Dwi Cahya (GLOBAL HEALTH SCIENCE GROUP, 2024)
The number of cases of excess weight among teenagers is still high. This places teenagers in a group at high risk of experiencing long-term health problems. The aim of writing a scientific paper is to analyze the application of GREW-DEAL innovation in family and community nursing. This study is a case study. The sample used was 10 managed families and 90 private high school students in Depok City. The results of 10 families showed an increase in the average knowledge from 15.6 to 19.0, then attitudes from 13.9 to 16.8 and skills from 21.2 to 29.2, then there was a decrease in the average BMI from 21.58. to 20.28 and increased family independence (100%) between pre and post scores. The application of GREW-DEAL to adolescents at school also shows an increase in average knowledge, attitudes and skills. Apart from that, there has been an improvement in healthy eating patterns, increased activity and physical exercise. The GREW-DEAL innovation is a recommendation for community nurses in preventing and controlling excess weight in adolescents and is the basis for developing other innovations within the scope of family and community nursing care.